Tipos de residuos orgánicos vegetales y de comida en la productividad de larvas de Hermetia illucens (diptera: stratiomyidae) como biodegradador en el mercado central, Loreto 2024 - Silva Lazaro, Aissa Nicole (2025)
Improper management of organic solid waste is a growing issue with significant environmental impacts. In the markets of Iquitos, the accumulation of waste such as fruit peels and food scraps has caused pollution and health risks, highlighting the need for sustainable alternatives. The aim of this research was to evaluate the effect of vegetable and food waste on the productivity of Hermetia illucens (black soldier fly) larvae as a biodegrader in the Central Market of Loreto. The study analyzed the quantity, weight of the larvae, and organic fertilizer production. A quantitative, explanatory approach was used with a pure experimental design, employing 480 kg of waste divided into two treatments: vegetable waste (VW) and food waste (FW). Results showed that larvae fed with vegetable waste had a higher quantity (3203.67 larvae vs. 3147.83) and weight (447.20 g vs. 416.95 g), although without significant differences. The production of manure was significantly higher with vegetable waste (2359.33 g vs. 2150.50 g). Additionally, vegetable waste showed higher efficiency in conversion to fertilizer (5.90% vs. 5.38%). It is concluded that both types of waste are viable for larvae and manure production, but vegetable organic waste offers greater efficiency in transformation, contributing to sustainable waste management in tropical regions.